Collaboration for the Internationalization of Research and Development: Opportunities for Colombia in the Post-Pandemic Term (2023)
Within the new world scenario, the internationalization of science, technology and innovation represents a fast track for the development of nations and the solution of the global challenges posed by the 2030 Agenda. The above reflects on the importance of science and technology as determining factors to promote sustainable development and especially to overcome any scenario of health and economic crisis generated by the Covid-19 pandemic, which has promoted the creation of programs that are in favor of investment in human resources and infrastructure to strengthen local capacities, long-term financing for the development of scientific and technological projects, as well as the implementation of new mechanisms that favor the institutionalization of science, technology and innovation policies.